Analysis of the Relationship Between Drug Stockout Incidents and the Use of Hospital Management Information System (SIMRS) Technology with Patient Satisfaction at the Pharmacy Installation of Bogor City Hospital - Shulihah, Shulihah; Thaha, Abdul Razak; Maududi , Abul A'la Al (Enrichment: Journal of Multidisciplinary Research and Development, 2025)
Drug stockouts remain a significant challenge in healthcare systems, particularly in hospital pharmacy installations, directly impacting patient treatment and satisfaction. Efficient drug inventory management is crucial to mitigating these incidents. The adoption of Hospital Management Information System (SIMRS) technology presents a potential solution to optimize inventory control and enhance service quality. This research analyzes the relationship between drug stockout incidents and the use of Hospital Management Information Systems (SIMRS) technology with patient satisfaction at the Pharmacy Installation of Bogor City Hospital. Drug stockouts significantly affect patient treatment and satisfaction, necessitating efficient drug inventory management. The research employs a cross-sectional analytical approach, collecting data from pharmacy personnel and patients through surveys. The findings indicate that drug stockouts occur frequently, influenced by factors such as delayed deliveries and payment issues. Conversely, the effective implementation of SIMRS technology enhances drug management efficiency and improves patient satisfaction. Statistical analysis reveals a significant correlation between the incidence of drug stockouts and patient satisfaction, as well as a strong positive impact of SIMRS usage on reducing stockouts. The study highlights the importance of optimizing SIMRS to ensure drug availability, thereby enhancing the quality of healthcare services.